Aplicativo mobile de chave de identificação de insetos integrado a glossário ilustrado de terminologias - Zimerer, Ana Paula Marinheiro (2022)
As a result of the great advances in the technological area in recent years, several sectors have been reinvented to keep up with such progress. Thus, the educational sector also underwent updates, which are even more evident in the pandemic context, where digital tools have become great allies and enablers of distance learning. Regarding of Biological Sciences courses, the use of websites and applications as teaching tools is uncommon, but it is known that the use of such tools as pedagogical mediators might make the teaching and learning process dynamic and interactive. At Unesp Rio Claro, the Invertebrates II course of the Biological Sciences undergraduate program is mainly characterized by the practical proposal of developing a collection of insects, posing several challenges as it is the first identification experience of the students. As a result of this observation, the present work seeks to fuse the benefits of practical classes with the dynamism of new technologies, developing an application for cell phones consisting of an identification key for the orders Orthoptera, Mantodea, Blattodea and Isoptera, accompanied by an illustrated dictionary of morphological terms.The development was divided in three stages: in the first, the database was developed through the SQL language on the SQLSERVER platform; in the second, the programming interface was structured, through the JAVA language in the Eclipse environment, and the creation screens and buttons, using the React language with the Visual Code Studio tool; last stage of tests and corrections. The publication took place in a free demo version, through the Surge platform.